The Effect of Matoa (Pometia Pinnata) Leaf Ethanol Extract on Reducing Blood Sugar Level in Male Mice (Mus Musculus) Induced by Alloxan - Pagarra, Halifah; Salsabila, Shopia; Muis, Abd; Naufal Syaiful Haq, Muhammad (Jurusan Biologi Universitas Negeri Makassar, 2025)
This research aims to determine the total phenolic content and antioxidant activity of the ethanol extract from Matoa (Pometia pinnata) leaves as well as its effect on blood sugar levels in male mice (Mus musculus) induced with alloxan. To determine total phenolic content using the Folin-Ciocalteu method, and the DPPH method to measure antioxidant activity. The effect of Matoa leaves on blood sugar reduction in mice used a completely randomized design (CRD) with 15 mice divided into 5 treatments with 3 replications: namely P1 (Extract 125 mg/kg BW), P2 (Extract 250 mg/kg BW), P3 (Extract 500 mg/kg BW), K+ (Glibenclamide), and K- (Na-CMC 0.5%). Extraction used the maceration method with 70% ethanol solvent. The results of the total phenolic test showed the presence of phenolics with a value of 26.24872 mg GAE/g. The measurement of antioxidant activity yielded an IC50 value of 1.961 ppm. The results of testing the blood sugar levels showed that there was an effect of giving ethanol extract of Matoa (Pometia pinnata) leaves on reducing blood sugar levels in male mice (Mus musculus). Giving of ethanol extract of Matoa leaves at a dose of 250 mg/kg BW is effective in reducing blood sugar levels. So it can be concluded that the ethanol extract of Matoa leaves has an effect on reducing blood sugar levels in male mice